A kinetic energy preserving DG scheme applied to mechanical FSI. Issue 1 (15th March 2018) - Ortleb, Sigrun
Abstract: In the context of mechanical fluid‐structure interaction (FSI) comprising moving or deforming structures, fluid discretizations need to cope with time‐dependent fluid domains and resulting grid deformations in addition to the general challenges regarding e.g. boundary layers and turbulent phenomena. Recent approaches in the simulation of compressible turbulent flow are based on so‐called split forms of conservation laws to guarantee the preservation of secondary physical quantities such as kinetic energy. For the simulation of turbulent flows, this often leads to a better representation of the kinetic energy spectrum. Initially, kinetic energy preserving(KEP) DG schemes have been constructed on Gauss‐Legendre‐Lobatto(GLL) nodes containing the interval end points, however, KEP DG schemes based on the classical Gauss‐Legendre(GL) nodes are potentially more accurate and may be also more efficient than its GLL variant for certain applications. In this work, the KEP‐DG schemes both on GL and GLL nodes are applied to the classical moving piston test case via an ALE formulation on moving fluid grids showing a more accurate frequency representation of the structure displacement in case of GLL nodes. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)